A Novel Orthoreovirus Isolated From Dead Stranded Harbor Seals From Puget Sound, Washington State, United States - Nielsen, Ole; Rodrigues, Thaís C. S.; Popov, Vsevolod L.; Subramaniam, Kuttichantran; Waltzek, Thomas B.; Lambourn, Dyanna M.; Raverty, Stephen (Frontiers in Marine Science, 2021)
As part of an ongoing investigation of harbor seal (Phoca vitulina) mortalities within Puget Sound, Washington State, United States, between October 2007 and July 2008, 25 seal cases were submitted for histopathology and ancillary diagnostic testing, including additional attempted virus isolation. In vitro granular and refractile cytopathic effects (CPE) were consistently observed in Vero.DogSLAMtag cells inoculated with tissue homogenates from three seals. Transmission electron microscopy of infected Vero.DogSLAMtag cells revealed cytoplasmic clusters of icosahedral viral particles morphologically consistent with members of the family Reoviridae. The complete genome of a novel species within the genus Orthoreovirus, tentatively named phocid orthoreovirus 1 (PhRV1), was determined by next-generation sequencing and confirmed by rt-PCR in isolates from the three harbor seals. This is the first report of an orthoreovirus infection associated with dead stranded harbor seals. Aside from the CPE and ultrastructural findings, no consistent signalment, gross pathology, histopathology, or ancillary diagnostic findings were identified with PhRV1 infection. Further research is needed to determine the prevalence, tissue tropism, transmission, pathogenicity, zoonotic potential, and host range of orthoreoviruses in pinnipeds. This study demonstrates the value of thorough necropsy investigations and a multidisciplinary team approach to advance our understanding of marine mammal health.